2019
DOI: 10.3390/app9153093
|View full text |Cite
|
Sign up to set email alerts
|

The Machine Learning-Based Dropout Early Warning System for Improving the Performance of Dropout Prediction

Abstract: A dropout early warning system enables schools to preemptively identify students who are at risk of dropping out of school, to promptly react to them, and eventually to help potential dropout students to continue their learning for a better future. However, the inherent class imbalance between dropout and non-dropout students could pose difficulty in building accurate predictive modeling for a dropout early warning system. The present study aimed to improve the performance of a dropout early warning system: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 26 publications
1
61
2
3
Order By: Relevance
“…Through a series of tests, the authors identified that the key attributes that affect student dropouts are mostly academic aspects, namely performance grade, quarterly exam rating, attendance percentage, and written score (e.g., quizzes, summative test). Such results are similar to the past data of Pereira and Zambrano [4], wherein the primary causes of student dropout attributed to the academic variables such as low academic grade. Also, the location or distance of the school from the students' residences has related factors of students' dropout.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Through a series of tests, the authors identified that the key attributes that affect student dropouts are mostly academic aspects, namely performance grade, quarterly exam rating, attendance percentage, and written score (e.g., quizzes, summative test). Such results are similar to the past data of Pereira and Zambrano [4], wherein the primary causes of student dropout attributed to the academic variables such as low academic grade. Also, the location or distance of the school from the students' residences has related factors of students' dropout.…”
Section: Resultssupporting
confidence: 90%
“…Sunbok Lee and Jae Young Chung [4] introduced a study aimed at improving the efficiency of the early warning system: (a) dealing with the problem of class imbalance using synthetic minority oversampling techniques (SMOTE) and set-up approaches in machine learning; and (b) testing qualified classifiers with both receiver operating characteristics (ROC) and precision-recall (PR) curves. Towards this purpose, they trained random forest, improved decision tree, random forest with SMOTE, and upgraded decision tree with SMOTE using huge data samples from 165,715 high school students from the National Education Information System (NEIS) in South Korea.…”
Section: Related Literaturementioning
confidence: 99%
“…As described in different systematic reviews [4,5], many models can be applied to education. Students' performance [6], students' dropout within an individual course [7,8], program retention [9], recommender systems in terms of activities [10], learning resources, [11] and next courses to be enrolled [12,13] are some examples of the application of those models. Independently of the desired outcome, models have used many different types of data in order to perform the predictions.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…These can allow faculties to improve the learning/teaching strategies and interactions to be employed in virtual courses. It may also allow researchers to make predictions about the students' behavior during their process of learning, such as preventing dropouts in courses [47].…”
mentioning
confidence: 99%